A gain-clamped S-band erbium-doped fiber amplifier using fiber Bragg grating - Yeh, CH; Lin, MC; Chi, S (My University, 2006)
We propose and investigate experimentally a gain-clamped S-band erbium-doped fiber amplifier module, employing a fiber Bragg grating to serve as a reflected element to lase a saturated tone injected into the module, by forward optical feedback method. In addition, different injected powers of the saturated tone are used to realize the performances of gain and noise figure for the proposed amplifier over the effectively wavelength range of 1478-1520 nm. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: FBG; S-band; gain clamping; EDFA